Riparina III é uma droga promissora no tratamento da depressão? - Mallmann, Auriana Serra Vasconcelos (2019)
Stress is crucially related to the pathophysiology of mood disorders, including depression. Since there is no effective therapy, research on new substances is paramount. In rodents, several findings have indicated that corticosterone administration induces behavioral and neurochemical aspects of depression. Recently, riparin III (Rip III) has shown antidepressant-like properties in trials performed on animal models. Thus, our goal was to investigate the Rip III effects in behavioral tests, monoamines levels, expression of AMPA and ERK, oxidative stress and cytokines levels in chronic corticosterone-induced model of depression. To do this, swiss mice were treated with subcutaneous administration of corticosterone for 21 days. In addition, for the last 7 days, Rip III or fluvoxamine were also administered per os in specific test groups. Control groups received subcutaneous saline injections or distilled water per os. At the end of the timeline, the animals were killed and their hippocampi, prefrontal cortex, and striatum dissected for neurochemical analysis. Brain changes following corticosterone administration were confirmed, and Rip III could reversed the most abnormal behavioral and neurochemical corticosterone-induced alterations. Our results highlighted the antioxidant, anti-inflammatory, anxiolytic and antidepressant pharmacological potential of Rip III.